Результаты сравнения разработанной теоретической модели нижней части области F ионосферы с эмпирической моделью А. Д. Данилова - Живолуп, Т. Г. (НТУ "ХПИ", 2004)
Comparison of the elaborated theoretical model of the ionosphere F-region lower part with the A. D. Danilov empirical model is considered. Comparison results of the experimental and theoretical height profiles give evidence about good accuracy characteristics of the elaborated theoretical model
Keywords: атмосфера; солнечное излучение; ионизация; атомарный кислород; молекулярные ионы